Applying the Rasch model : fundamental measurement in the human sciences - Bond, Trevor G.; Fox, Christine M (Mahwah, N.J. : Lawrence Erlbaum Associates Publishers, 2007)
"Written In an accessible style, this book facilitates a deep understanding of the Rasch model a theoretically elegant, yet straightforward method for explaining Interactions between observed and latent variables. Authors Bond and Fox review the crucial properties of the Rasch model and demonstrate its use with a wide range of examples Including the measurement of educational achievement, human development, attitudes, and medical rehabilitation. A glossary and numerous Illustrations further aid the reader's understanding of the Important measurement Issues. The authors' goals are to present an accessible overview of Rasch analysis that does not require a statistical background. They demonstrate how to apply Rasch analysis and prepare readers to perform their own analyses and Interpret the results."--Jacket
1. Why measurement is fundamental -- 2. Important principles of measurement made explicit -- 3. Basic principles of the Rasch model -- 4. Building a set of items for measurement -- 5. Invariance : a crucial property of scientific measurement -- 6. Measurement using Likert scales -- 7. The partial credit Rasch model -- 8. Measuring facets beyond ability and difficulty -- 9. Development, education, and rehabilitation : change over time -- 10. The Rasch model applied across the human sciences -- 11. Rasch modeling applied : rating scale design -- 12. Model fit and unidimensionality -- 13. A synthetic overview -- App. A. Technical aspects of the Rasch model
System requirements for accompanying CD-ROM: Version of latest Windsteps program and the data files for the book's examples
Includes bibliographical references (pages 315-329) and indexes
Keywords: Psychology -- Statistical methods; Social sciences -- Statistical methods; Psychology -- Research -- Methodology; Social sciences -- Research -- Methodology